Analyzing Physicochemical Properties of Wild Grapes (Lannea Microcarpa) Seed Oil - A. A. Warra (Faculty of Engineering and Technology, Sampoerna University, 2019)
The purpose of this study was to analyze physicochemical properties of wild grape (Lannea microcarpa) seed oil. Several characterizations were conducted, including a gas chromatography and mass spectrometry (GC-MS) and cold saponification. The analyses were also supported by measuring acid, iodine, saponification, and peroxide values. Other analyses were relative density and refractive index. Experimental results showed that the oil was dark purple with the composition of oil of 59%. The qualitative GC-MS revealed the oil contained several fatty acids, including decanoic acid, palmitic acid, stearic acid, margaric acid, 1-octadecanoic acid, oleic, and erucic acid. The soap produced from the seed oil has basic pH and relatively high foam value. When the high concentration of oil was used, the appearance of oil was very dark purple and slightly soluble in water. This is due to the fact that most of the oil compositions were non-polar structure. This result confirmed the potential use of the oil for soap and other cosmetic materials.